2022
DOI: 10.1002/admi.202201751
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Plasmoelectric Effect in Plasmonic Zirconium Nitride

Abstract: silicon-gold (Si-Au) interface can harvest near-infrared light longer than 1100 nm, [1] allowing near-infrared photodetection using Si-based structures with improved efficiencies. Sub-bandgap excitation is not limited to Si; other semiconductors such as germanium, [2] III-V semiconductors, [3] and oxide semiconductors [4] have also demonstrated subbandgap hot-carrier excitations when they form heterojunctions with metals. What is common among these demonstrations is that hot carrier excitations are drastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Indeed, few authors have reported processes to pattern ZrN films. E-beam lithography and dry etching [25] or scanning probe microscopy oxidation and hydrofluoric acid etching [26] were used for this purpose, but these techniques are time consuming, use toxic products, and are expensive. Conversely, sol-gel ZrO 2 can be easily structured by UV exposure [27], thereby making it possible to create ZrN micro-nanostructured thin films with complex shapes after nitridation.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, few authors have reported processes to pattern ZrN films. E-beam lithography and dry etching [25] or scanning probe microscopy oxidation and hydrofluoric acid etching [26] were used for this purpose, but these techniques are time consuming, use toxic products, and are expensive. Conversely, sol-gel ZrO 2 can be easily structured by UV exposure [27], thereby making it possible to create ZrN micro-nanostructured thin films with complex shapes after nitridation.…”
Section: Introductionmentioning
confidence: 99%